Perlindungan Hukum Terhadap Pelaku Tindak Pidana Yang Menjadi Korban Penganiayaan Massa - Frits Jesaldi Leunupun; Sherly Adam; Iqbal Taufik (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Indonesia as a state of law is obliged to provide legal protection for citizens who get acts of violence or persecution both as perpetrators and as victims of criminal acts.Purposes of the Research: This study aims to analyze and discuss legal protection arrangements for criminals who are victims of mass persecution in criminal law in Indonesia and analyze and discuss forms of legal protection for criminals who are victims of mass persecution. Methods of the Research: The research method used is normative juridical research. The problem approach used is the statutory approach, the conceptual analysis approach and the case approach. The legal materials used are primary and secondary legal materials. The collection technique uses a literature study as well as processing techniques and analysis of legal materials through description using qualitative methods.Results of the Research: The results of the study indicate that the regulation of legal protection for perpetrators of criminal acts who are victims of mass has not been clearly regulated because the legal protection arrangements in the legislation for victims to become perpetrators of criminal acts are still separate, where the arrangements for victims and perpetrators are still separate. criminal acts are regulated respectively in the laws and regulations of criminal law in Indonesia and forms of legal protection for perpetrators of criminal acts who are victims of mass persecution include medical services and restitution, medical services are provided to victims of crime by undergoing treatment in hospitals and restitution namely the provision of compensation given by the defendant/perpetrator to the victim of a crime because even though it is the perpetrator of a crime who later becomes a victim, protection can be given as a manifestation of the protection of human rights.